Study on the substitutability of nighttime light data for SDG indicators: a case study of Yunnan Province - Quan, Xuefeng; Song, Xiaoyu; Miao, Junxia; Huang, Chunlin; Gao, Feng; Li, Jie; Ying, Luyao (Frontiers in Environmental Science, 2023)
Data acquisition is the main bottleneck in the evaluation of sustainable development goals (SDGs). The nighttime light intensity is closely associated with human social activities, and studying its substitutability for SDG indicators in measurement can help to expand evaluation methods and solve data acquisition difficulties. Through a case study of Yunnan Province, China, this paper aims to find applicable substitutive indicators in areas with a weak data base by exploring the relationship between SDG indicators and nighttime light, to realize diversified evaluation on specific SDGs, and to further reduce the evaluation cost. The study indicates that when the SDG indicators are classified into economic, social and environmental categories, the total value of nighttime light presents a significant correlation and substitutability with economic indicators; significantly correlated with some social indicators, it can reveal the weak links in the development of underdeveloped areas; it is not significantly correlated with environmental indicators, while a trend correlation exists, which can provide some reference values.